2019
DOI: 10.4103/psychiatry.indianjpsychiatry_451_18
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives, attitude, and practice of lithium prescription among psychiatrists in India

Abstract: Introduction:Lithium “the magic pill” past its discovery remained the respite for patients with bipolar disorders for decades. The prescriptions of lithium were replaced by other drugs because of the cumbersome monitoring, adverse effect profile, narrow therapeutic index, and frequent comorbidities in patients. The objectives of this study were to understand the knowledge, attitude, and practice of lithium by a subset of psychiatrists in India, which will help us understand the theory–practice gap and for devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…In general, our results indicating that clinicians use lithium in more than 50% of their BD patients as maintenance treatment are in line with previous reports and registries from diverse countries (Lin et al 2022 ; Mandal et al 2019 ; Pacciardi et al 2017 ; Pérez de Mendiola et al 2021 ; Sköld et al 2021 ). However, there is a striking diversity of prescriptions patterns among different countries (Kessing 2019b ), with some countries and regions having lithium prescription patterns below 50% (Grover et al 2021 ; Heeren et al 2011 ; Karanti et al 2016 ; Lyall et al 2019 ) or above (Bohlken et al 2020 ; Pérez de Mendiola et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In general, our results indicating that clinicians use lithium in more than 50% of their BD patients as maintenance treatment are in line with previous reports and registries from diverse countries (Lin et al 2022 ; Mandal et al 2019 ; Pacciardi et al 2017 ; Pérez de Mendiola et al 2021 ; Sköld et al 2021 ). However, there is a striking diversity of prescriptions patterns among different countries (Kessing 2019b ), with some countries and regions having lithium prescription patterns below 50% (Grover et al 2021 ; Heeren et al 2011 ; Karanti et al 2016 ; Lyall et al 2019 ) or above (Bohlken et al 2020 ; Pérez de Mendiola et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesize that this finding might reflect the psychiatrists' reluctance to prescribe lithium for patients who have hypothyroidism. This hypothesis is aligned with another study indicating that psychiatrists were skeptical about starting lithium due to several perceived barriers, among which are the adverse effects [26].…”
Section: Discussionsupporting
confidence: 83%
“…Some reasons for this trend of decreased lithium use include its adverse effects and narrow therapeutic index [21], with a significant risk of toxicity at levels only 2-3 times above its therapeutic dose [22]. These concerns have been validated by physician opinion studies, which found low adherence to serum-level monitoring and side effects to be the most significant considerations that influenced lithium prescription in their practice [23,24]. There are also possible adverse effects on renal function and fetal growth, and its use in populations such as the elderly and pregnant women requires careful consideration of the risks and benefits [22].…”
Section: Introductionmentioning
confidence: 99%